Using Augmented Reality to Reinforce the Learning of Installation of Electrical Equipment and Machines - Jadán-Guerrero, Janio (2022)
The educational level of technical high schools has been affected by the current state of emergency caused by the Covid-19 pandemic, due to the lack of educational resources for subjects that require laboratory practice. The objective of the research is to describe a pedagogical strategy using interactive support material focused on augmented reality for equipment installations and electrical machines learning, in order to supply the lack of laboratories. The research carried out surveys to seven teachers, who teach practical subjects, and evaluations to 60 students who underwent the intervention with the application of augmented reality. The results of the pre-test and post-test were analyzed to verify the stated objectives, demonstrating that there are motivating results with the application of two tools Mywebar and Assemblr in the performance of the classes, affirming that the augmented reality tool impacts and motivates the teaching-learning process in the technical area in the professional figure of installations, equipment and electrical machines in a favorable way.